NECESSITY FOR THE DEVELOPMENT OF MEDIUM-SIZED ENTERPRISES IN HOCHIMINH CITY: A CASE STUDY OF THE ELECTRONIC AND INFORMATION TECHNOLOGY AND MECHANICAL SECTORS - Nguyễn, Thị Thanh Uyên (Trường Đại học Đà Lạt, 2023)
This study aims to investigate the absence of medium-sized enterprises and the necessity for the development of medium-sized enterprises in two capital-intensive sectors: Electronic and Information Technology and Mechanics in Hochiminh City. The results reveal two major issues. First, there is a lack of medium-sized enterprises in the two targeted sectors. Second, medium-sized enterprises are proven to play an important role in generating and utilizing more effective resources than other large-scale enterprises including the ability to mobilize capital, obtain technology, gain market access and policy support, linking resources, generating income and higher productivity. The case study offers some policy recommendations to overcome the lack of medium-sized enterprises in Hochiminh City.